Quality and Shelf Life of Dressed Chicken from Different Sources under Refrigeration (4±1OC) - Kumar, H.T. Santosh; Pal, U.K.; Mandal , P.K.; Das , C.D. (Journal of Meat Science, 2016)
A study was carried out to examine the changes in quality of dressed chicken obtained from different sources of processing during storage under refrigeration at 4±1OC for 9 days. During storage at 4±1OC, pH of the samples (RSC: Road side slaughtered chicken; MSC: Market slaughtered chicken and SSC: Scientifically slaughtered chicken) decreased on day 3 of storage followed by gradual but significant (p<0.05) increase on day 9 of storage. Extract release volume (ERV) decreased non-significantly in all the samples up to 6th day followed by significant (p<0.05) decrease in RSC and SSC samples on 9th day of storage. There was significant increase (p<0.05) in TBA and Tyrosine values of all three samples during storage. SSC samples showed lower TBA and Tyrosine values throughout storage compared to RSC and MSC samples. Compared to RSC and MSC samples, SSC samples showed significantly lower (p<0.005) total viable count (TVC), coliform count, psychrophilic count (PPC) and yeast and moulds count (YMC) at initial stage and the same trend continued on subsequent days of storage. Sensory scores for attributes viz. appearance, flavour, texture, juiciness and overall palatability did not show any differences among the samples except on day 1 only for overall palatability. RSC and MSC samples were spoiled on 6th day while SSC samples got spoiled on 9th day indicating that SSC samples had better quality and shelf life under refrigeration (4±1OC) storage compared to samples from other two sources.